2nd Generation car security system (2GCSS) : Embedded car security system - Rahman, Md. Mashiur; Nahid, Md. Kudrat Ullah (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.